Highly sensitive wearable 3D piezoresistive pressure sensors based on graphene coated isotropic non-woven substrate. (February 2019) - Lu, Yunjing; Tian, Mingwei; Sun, Xuantong; Pan, Ning; Chen, Fuxing; Zhu, Shifeng; Zhang, Xiansheng; Chen, Shaojuan
Abstract: Piezoresistive pressure sensors are deemed as a critical sensing component in wearable devices, and various polymer assembly with different structures are selected as flexible sensor substances. In this paper, low cost, commercial three-dimensional polyester non-woven fabrics (PNWFs) were employed as the sensor substrate whose advantages were elucidated through mathematical analysis. The effects of structure parameters (fiber diameter and fiber volume fraction) of 3D non-woven sensors on the sensing performance were analyzed. Reduced graphene oxide (rGO) and polydimethylsiloxane (PDMS) were deposited on the substrate to form the piezoresistive pressure sensor with a high conductivity 0.29 S/m after thermal reduction treatment. The assembled pressure sensors in general possessed excellent sensing characteristics, including excellent sensitivities of compressing (S = 23.41 kPa −1 ) and bending (S = 35.37 kPa −1 ), short response time (120 ms) and recovery time (240 ms), favorable resolutions (18 Pa under compressing and 21 Pa under bending) and low hysteresis value (0.8%). Finally, the pressure sensor has demonstrated successfully in detecting various physiological activities and subtle physiological signals, including walking, running, elbow flexing, finger bending, breathing, speaking and blood pulse beating.